1978
DOI: 10.1177/014107687807100206
|View full text |Cite
|
Sign up to set email alerts
|

Tonsils and Adenoids: What do we Find?

Abstract: In the last twelve months, 216 pairs of paiatine tonsils were removed in the Ear, Nose and Throat Department of Manchester Royal Infirmary. These operations were usually in children, from whom adenoid tissue (the pharyngeal tonsil) was removed at the same time. In the absence of a special reason, neither tonsils nor adenoids from children find their way to the surgical histology department: this is true enough to require special requests for specimens so that other people can see these organs. Adult tonsils ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
4

Year Published

1978
1978
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
3
3
0
4
Order By: Relevance
“…Woodruff found same findings as an exuberant cryptitis and intact tonsillar architecture (4). Wright and Alvi also found same findings as cryptitis and lymphoid hyperplasia in tonsils from patients with chronic tonsillitis (5,6).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Woodruff found same findings as an exuberant cryptitis and intact tonsillar architecture (4). Wright and Alvi also found same findings as cryptitis and lymphoid hyperplasia in tonsils from patients with chronic tonsillitis (5,6).…”
Section: Discussionsupporting
confidence: 58%
“…Although chronic tonsillitis are still the most common reasons for tonsillectomy (1), histopathological criteria for this infection have not been well studied. All investigations were confined to the lymphoid follicle, germinal centre and crypts, rather than investigating the changes in the entire tonsil area including surface epithelium (1)(2)(3)(4)(5)(6)(7)(8). Thus the results from these studies have been inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, Beverley et al showed that lymphadenopathy due to postnatally acquired toxoplasma infection is seen more frequently in males under 15 yr, in females over 25 yr and equally in the two sexes between these ages. Similar results are seen with tonsillectomy (Wright, 1978). In an experimental study in mice, Henry and Beverley drew attention to the greater height of the lymphnode post-capillary venules in females, both in control and infected animals.…”
Section: On Responses Transacted By B Cellssupporting
confidence: 52%
“…Dezennium sind Jungen, im 2. Mäd-chen stärker vertreten [5,7,15,19,23,24]. Venters und Bloor [19] oder Wright [24] zählten in ihrem Krankengut mehr als doppelt so viel tonsillektomierte Frauen zwischen 15 und 19 Jahren wie gleichaltrige Männer.…”
Section: Zur Tonsillektomiehäufung Bei Jungen Frauenunclassified
“…Diese Beobachtungen führen zwangsläufig zu der Vermutung, dass psychopathologische Faktoren zumindest teilweise eine wesentliche Rolle bei der Indikationsstellung zur Tonsillektomie spielen und unser Persönlichkeitsscreening mit dem FPI-R bei 24 Ob diese Auslegung der Textergebnisse zutrifft, mag dahingestellt bleiben, jedoch halten wir es angesichts der Persönlich-keitsprofile für wahrscheinlich, dass bei manchen jungen Frauen die besondere Persönlichkeitsstruktur in der psychosensiblen postpubertären Altersstufe die Indikation zur Tonsillektomie maßgeblich beeinflusst.Klar muss dabei bleiben,dass die Interpretation der Resultate des FPI-R nur mit gewisser Zurückhaltung erfolgen darf: einerseits steht eine relativ kleine Gruppe von nur 24 Probandinnen einem sehr viel größeren Vergleichskollektiv (n=169) gegenüber. Andererseits stimmt der Altersbereich der Normstichprobe (16-24 Jahre) nicht exakt mit dem der untersuchten Frauengruppe überein,wenngleich das Phäno-men der höheren Tonsillektomierate auch die Altersgruppe der Frauen von 20-25 Jahren betrifft (⊡ Abb.1,2).…”
Section: Diskussionunclassified